Changes in the distribution of F-latency (DFL) for different postures of head and neck (Bangladesh Journal of Medical Physics, 2018)
Distribution of F-Latency (DFL) is a new neurological parameter conceived by the Biomedical Physics group of Dhaka University. Previous experimental studies have indicated that DFL, obtained from median nerve, varies with postures of the subject, particularly with the bending of the head. It agreed with the contention that bending of head might produce compression or stretching of nerve fibers as they come out of the vertebra, and that DFL is a sensitive parameter that gets affected by even such temporary changes. The present work was taken up with two objectives, i) to improve upon the earlier work by taking measurements with a few specific angles of head bending, particularly in the left and right directions, and ii) to provide a verification of earlier results. For bending of head to left and right sides, we chose 300 and 450 respectively. For forward and backward directions the angles were not measured and the subjects were asked to bend as much as they could without going beyond a comfort level. The study was carried out on 6 student volunteers aged between 24 and 26. The DFLs obtained with different postures of the head were analyzed to look for systematic trends in the changes, if any. Changes in several parameters like peak, mean, standard deviation, skewness and half-width in the rising and falling edges (down to 50 % height of the peak) were studied for different postures of head and neck which showed consistent changes.Bangladesh Journal of Medical Physics Vol.9 No.1 2016 1-10